Analysis of Student Discipline Program Development at Muhammadiyah 1 Taman Sidoarjo Vocational High School - Irsyad Dwilinanto Herawansyah; Anita Puji Astutik (Universitas Muhammadiyah Sidoarjo, 2022)
This study uses a qualitative research approach in which the researcher describes the research results in the form of words or sentences. The subjects in this study were principals, waka students, PAI teachers, BK teachers, and students. The types and sources of data obtained in this study are primary data sources and secondary data sources. While the data collection techniques are observation, interviews, and documentation. Data analysis and interpretation techniques use data reduction, data presentation and conclusion drawing. The results of this study indicate that to formulate or plan a student discipline program at SMK Muhammadiyah 1 Taman Sidoarjo from the provincial education office and then modified by the school, as well as the father or mother of the teacher and adapted to the conditions in the school. The regulation has been regulated in the Minister of National Education Number: 20 of 2007. If the student's violation points reach 15 points, the student will receive an oral warning. If you have reached 20 points, then students will get a written warning. If the points are 25-40 points, then students will get a summons for their parents or guardians. If the student's parents or guardians are unable to attend, a home visit will be held, where the teacher will go to the student's house to meet the student's parents or guardian and make a statement so that the student does not repeat the violation. The maximum number of points collected by students is 100.